Valuation of the general public's willingness to pay for the ecosystem services generated by on farm conservation of quinoa agrobiodiversity - CGIAR Research Program on Policies, Institutions, and Markets (2018)
The choice experiment survey of the general public was conducted in three Peruvian regions.